Committee on Environmental Effects of Organization Behavior. (The Accounting Review, 1973)
The article presents a report of the Committee on environmental effects of organization behavior of the American Accounting Association as of October 1973 on the measurement and reporting methods useful in communicating to internal and external users the effects of an organization's behavior on the physical environment. Accountants must begin to look beyond the firm (the client) to macro-entities to properly understand the consequences of accounting models. Asset values are partially dependent upon so-called free economic goods (air, water, etc,). The accountant of tomorrow must be committed and equipped, via education and experience, to help society solve environmental problems. This means, among other things, that the accountant must understand the social and behavioral ramifications of environmental data capture and communication. Accounting for and attesting to environmental information raises this argument-separation of management advisory services and auditing once more.